Respuesta :
Answer:
-2a³ + 9a² + 6ab² + 45a + 18b²
Step-by-step explanation:
(a + 3)×(−2a² + 15a + 6b²) =
= a×(−2a² + 15a + 6b²) + 3×(−2a² + 15a + 6b²) =
= -2a³ + 15a² + 6ab² - 6a² + 45a + 18b² =
= -2a³ + 9a² + 6ab² + 45a + 18b²
The product [tex](a+3) * (-2a^2+15a+6b^2)[/tex] is [tex]-2a^3+9a^2+ 45a +6ab^2 + 18b^2[/tex]
What is product?
The product of numbers or expressions is gotten by multiplying them
The product expression is represented as:
[tex](a+3) * (-2a^2+15a+6b^2)[/tex]
Expand the expression
[tex]-2a^3+15a^2+6ab^2 -6a^2 + 45a + 18b^2[/tex]
Collect like terms
[tex]-2a^3+15a^2 -6a^2+ 45a +6ab^2 + 18b^2[/tex]
Evaluate the like terms
[tex]-2a^3+9a^2+ 45a +6ab^2 + 18b^2[/tex]
Hence, the product [tex](a+3) * (-2a^2+15a+6b^2)[/tex] is [tex]-2a^3+9a^2+ 45a +6ab^2 + 18b^2[/tex]
Read more about products at:
https://brainly.com/question/4344214